Respuesta :
x^2 - 5x = 12
x^2 - 5x + 6.25 = 12 + 6.25
(x - 2.5)^2 = 18.25
x - 2.5 = (+-) sqrt 18.25
x = 2.5 (+ - ) 4.27
x = 2.5 + 4.27 = 6.77 <==
x = 2.5 - 4.27 = -1.77 <==
x^2 - 5x + 6.25 = 12 + 6.25
(x - 2.5)^2 = 18.25
x - 2.5 = (+-) sqrt 18.25
x = 2.5 (+ - ) 4.27
x = 2.5 + 4.27 = 6.77 <==
x = 2.5 - 4.27 = -1.77 <==
Answer:
[tex]x=6.77[/tex] and [tex]x=-1.77[/tex]
Step-by-step explanation:
The given equation is:
[tex]x^2-5x=12[/tex]
Adding [tex]6.25[/tex] on both sides of the above equation, we get
⇒[tex]x^2-5x+6.25=12+6.25[/tex]
⇒[tex](x-2.5)^2=18.25[/tex]
⇒[tex](x-2.5)={\pm}{\sqrt{18.25}[/tex]
⇒[tex](x-2.5)={\pm}4.27[/tex]
⇒[tex](x-2.5)=4.27[/tex] and [tex](x-2.5)=-4.27[/tex]
⇒[tex]x=4.27+2.5[/tex] and [tex]x=-4.27+2.5[/tex]
⇒[tex]x=6.77[/tex] and [tex]x=-1.77[/tex]
which is the required values of x.